Obligation of Madiyah Maintenance After Divorce: Perspectives of Islamic Law and Positive Law - Nugraha, Iqbal Subhan; Aziz, Abdul (Sharia Journal and Education Center Publishing, 2024)
Abstract This study focuses on the obligation of post-divorce alimony from the perspective of Islamic law and positive law, considering the importance of this issue in the context of social justice and the protection of women's rights. The background of this study is based on the many cases where ex-wives have difficulty demanding alimony after divorce, which is often triggered by a lack of legal understanding and social stigma. The purpose of this study is to analyze the obligation of madiyah maintenance and the challenges faced in its implementation, with the hope of providing recommendations for the improvement of the legal and social system that supports women's rights. The method used in this study is a qualitative approach, with a juridical-normative approach. The findings show that there is a gap between Islamic law and positive law in enforcing the obligation of madiyah alimony, as well as the existence of social stigma that hinders ex-wives from fighting for their rights. The conclusion of this study recommends the need for collaboration between the government, legal institutions, and the community to increase awareness about livelihood rights, strengthen the mediation system, and expand access to legal aid. With these steps, it is hoped that the obligation of alimony can be carried out more effectively, provide adequate protection for ex-wives and their children, and create a fairer and more equal society. Keywords: Madiyah Maintenance, Divorce, Islamic Law, Positive Law Abstrak Penelitian ini berfokus pada kewajiban nafkah madiyah pasca perceraian dari perspektif hukum Islam dan hukum positif, mengingat pentingnya isu ini dalam konteks keadilan sosial dan perlindungan hak-hak perempuan. Latar belakang penelitian ini didasarkan pada banyaknya kasus di mana mantan istri kesulitan menuntut nafkah setelah perceraian, yang sering kali dipicu oleh kurangnya pemahaman hukum dan stigma sosial. Tujuan penelitian ini adalah untuk menganalisis kewajiban nafkah madiyah serta tantangan yang dihadapi dalam implementasinya, dengan harapan dapat memberikan rekomendasi untuk perbaikan sistem hukum dan sosial yang mendukung hak-hak perempuan. Metode yang digunakan dalam penelitian ini adalah pendekatan kualitatif, dengan pendekatan yuridis-normatif. Hasil temuan menunjukkan bahwa terdapat kesenjangan antara hukum Islam dan hukum positif dalam menegakkan kewajiban nafkah madiyah, serta adanya stigma sosial yang menghambat mantan istri untuk memperjuangkan hak-haknya. Kesimpulan dari penelitian ini merekomendasikan perlunya kolaborasi antara pemerintah, lembaga hukum, dan masyarakat untuk meningkatkan kesadaran tentang hak-hak nafkah, memperkuat sistem mediasi, dan memperluas akses terhadap bantuan hukum. Dengan langkah-langkah ini, diharapkan kewajiban nafkah madiyah dapat terlaksana secara lebih efektif, memberikan perlindungan yang memadai bagi mantan istri dan anak-anak mereka, serta menciptakan masyarakat yang lebih adil dan setara. Kata Kunci: Nafkah Madiyah, Perceraian, Hukum Islam, Hukum Positif